TINDAK TUTUR REPRESENTATIF DAN MAKNA KIAS PADA SIARAN TELEVISI LAPOR PAK TRANS 7 - Amilia Sanggar Wati; Rina Devianty (Universitas Negeri Makassar, 2024)
The purpose of this research is to describe the form of representative speech acts and their figurative meaning in the television program Lapor Pak Trans 7. In this research, the type of research used is qualitative. The data source for this research is the utterances in the broadcast of Lapor Pak on Trans 7. Data collection uses listening, recording, and analysis techniques. The data analysis technique used in this research is content analysis. The result shows that the form of representative speech acts in the Lapor Pak Trans 7 television show consists of the speech acts of stating, telling, explaining, refusing, suggesting, complaining, mentioning, and speculating. Furthermore, there is the use of figurative meaning, namely the figurative meaning of personification, the figurative meaning of metaphor, the figurative meaning of metonomia, and the figurative meaning of irony.